Analysis of expected value of connectivity indices of random 2T2 kink chains - Ling, Xuemin; Razzaque, Asima; Khalil, Maham; Kanwal, Salma; Noor, Saima; Nazir, Robina (Frontiers in Physics, 2025)
In this work, we calculated the product connectivity index of three structures for the T2-type twists and formulated expressions of expected values of the forgotten index, atom bond connectivity index, sum connectivity index, product connectivity index and geometric arithmetic index of these random structures in the (ή−2) stage. In addition, we calculated the expected values numerically, graphically and analytically and found the topological indices that have the maximum and minimum value.